Knowledge risk and its mitigation : practices and cases - Lee, W. B.; Yip, Jessica Y. T.; Shek, Vivien W. Y. (Emerald Publishing Limited, 2021)
The life cycle of companies and enterprises, at present, is short-lived due to rapid social and technological changes. Despite the growing awareness on the importance of knowledge management (KM) among academic researchers, it is still not widely practiced in industry. Why is this?